(untitled) (Research, Society and Development, 2025)
Sexually Transmitted Infections (STIs) represent a global public health challenge, with AIDS being one of the most concerning, especially in the Northeast region of Brazil. This study aims to analyze how primary health care influences the incidence of AIDS cases caused by HIV in the Northeast of Brazil, highlighting the importance of developing this public sector to improve the quality of life of the northeastern population. The methodology used was a bibliographic review based on articles published between 2020 and 2025, obtained from databases such as Medline, Lilacs, Virtual Health Library (BVS), Google Scholar, and CAPES Journals. The results show that the Northeast faces challenges in accessing healthcare, exacerbated by Cuba’s withdrawal from the Mais Médicos program, the lack of medical training, and the unequal distribution of professionals. Additionally, medical precariousness, prejudice, and social stigma hinder diagnosis and treatment. It is concluded that strengthening primary care is essential to reduce the incidence of HIV/AIDS, improve access to early diagnosis, and ensure adequate treatment, contributing to the quality of life of the northeastern population. This study sought to portray HIV cases in the Northeast, address the distribution of these infection cases, and emphasize the importance of continuous observation of the pathology.